Theoretical Frame of Trust and Relationship Commitment in Supply Chains - Sonja Mlaker Kač (Naše gospodarstvo/Our economy, 2013)
In this article, we theoretically discuss the notion of trust and relationship commitment, emphasizing these concepts in connection with a good supply chain management. We present different views and theories that discuss trust and relation- ship commitment, especially in the context of interorganizational relationships, such as supply chains. We ultimately try to build a model for the further research of relationships in supply chains in Slovenia.